Mechanical walking aid for common knee problem - Chiam, Toon Fung (Nanyang Technological University, 2020)
The project aims to study the current sport and health care technologies targeting at Singapore elderly population. With the national interest to promote sports participation rate, research from National Sports Participation Survey (NSPS), seniors not participating in sport is mainly due to lack of interest and long-term physical disability. A further study conducted by the National health care also highlights the 1: 5 seniors experience chronic pain with a commonly affected area such as the knees and ankles. Therefore, the project also aims to produce a new prototype product to reduce the effect and enhance the user experience when engaging in daily activities such as walking, climbing stairs, and simple exercises. The paper shall first focus on literature review where the author looks into the common causes for an ageing knee problem and how excessive weight affects the joint using research from national sports participation survey and national health care group. The review will also look into current health care technologies targeting the common knee problem. The prototype design eleoved on a morphological chart, with springs as its main driving component using body weigh to act as a compressive force, the returning of the spring helps reduce the strength required on end-user. With the repeating of the motion, the device will allow its user to move the knee freely. As a result, the device helps reduce stress to the knee while doing the daily locomotive task. The design itself should only relive 50% of average user weight. However, the device's physical prototype was unable to complete due to Covid-19 global pandemic where movement restrictions order putting a stop to all Singapore non-essential business from February to July. Therefore, testing the prototype would be based on SolidWorks simulation software where the components' stress and strain were tested based on the software. The test result of the physical device will not deviate too much from the simulated device. Future work for this project can also consider working in groups to work on different design methods that allow better ideas and creative concept design to generate, which would eventually lead to an improvement in the device's overall outlook to be more aesthetically pleasing. The future improves device can also gather groups of volunteers to study the device overall stride length, and forces needed to stand upright and comfortability while wearing the whole device day.